Neuroprotection Against MPP+-Induced Cytotoxicity Through the Activation of PI3-K/Akt/GSK3β/MEF2D Signaling Pathway by Rhynchophylline, the Major Tetracyclic Oxindole Alkaloid Isolated From Uncaria rhynchophylla - Hu, Shengquan; Mak, Shinghung; Zuo, Xialin; Li, Haitao; Wang, Yuqiang; Han, Yifan (Frontiers in Pharmacology, 2018)
Rhynchophylline is a major tetracyclic oxindole alkaloid in Uncaria rhynchophylla, which has been extensively used as traditional herb medicine for the prevention of convulsions and hypertension. However, there is still little evidence about the neuroprotective effects of rhynchophylline for Parkinson’s disease (PD), a neurodegenerative condition currently without any effective cure. In this present study, the neuroprotective molecular mechanisms of rhynchophylline were investigated in a cellular model associated with PD. It is shown that rhynchophylline (10-50 µM) greatly prevented neurotoxicity caused by 1-methyl-4-phenylpyridinium ion (MPP+) in primary cerebellar granule neurons, as evidenced by the promotion of cell viability as well as the reversal of dysregulated protein expression of Bax/Bcl-2 ratio. Very encouragingly, we found that rhynchophylline markedly enhanced the activity of the transcription factor myocyte enhancer factor 2D (MEF2D) at both basal and pathological conditions using luciferase reporter gene assay, and reversed the inhibition of MEF2D caused by MPP+. Additionally, pharmacological inhibition of PI3-Kinase or short hairpin RNA-mediated gene down-regulation of MEF2D abrogated the protection provided by rhynchophylline. Furthermore, Western blot analysis revealed that rhynchophylline could potentiate PI3-K/Akt to attenuate GSK3β (the MEF2D inhibitor) in response to MPP+ insult. In conclusion, rhynchophylline inhibits MPP+-triggered neurotoxicity by stimulating MEF2D via activating PI3-K/Akt/GSK3β cascade. Rhynchophylline is served as a novel MEF2D enhancer and might be a potential candidate for further preclinical study in the prevention of PD.